Novel mycoplasma nucleomodulin MbovP475 decreased cell viability by regulating expression of CRYAB and MCF2L2 - Zhao, G.; Lu, D.; Wang, S.; Zhang, H.; Zhu, X.; Hao, Z.; Dawood, A.; Chen, Y.; Schieck, Elise G.; Hu, C.; Chen, X.; Yang, L.; et al. (Informa UK Limited, 2022)
Nucleomodulins are secreted bacterial proteins whose molecular targets are located in host cell nuclei. They are gaining attention as critical virulence factors that either modify the epigenetics of host cells or directly regulate host gene expression. Mycoplasma bovis is a major veterinary pathogen that secretes several potential virulence factors. The aim of this study was to determine whether any of their secreted proteins might function as nucleomodulins. After an initial in silico screening, the nuclear localization of the secreted putative lipoprotein MbovP475 of M. bovis was demonstrated in bovine macrophage cell line (BoMac) experimentally infected with M. bovis. Through combined application of ChIP-seq, Electrophoretic mobility shift assay (EMSA) and surface plasmon resonance (SPR) analysis, MbovP475 was determined to bind the promoter regions of the cell cycle central regulatory genes CRYAB and MCF2L2. MbovP475 has similar secondary structures with the transcription activator-like effectors (TALEs). Screening of various mutants affecting the potential DNA binding sites indicated that the residues 242NI243 within MbovP475 loop region of the helix-loop-helix domain were essential to its DNA binding activity, thereby contributing to decrease in BoMac cell viability. In conclusion, this is the first report to confirm M. bovis secretes a conserved TALE-like nucleomodulin that binds the promoters of CRYAB and MCF2L2 genes, and subsequently down-regulates their expression and decreases BoMac cell viability. Therefore, this study offers a new understanding of mycoplasma pathogenesis.